Madagascar : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This paper analyzes the basic data, social and demographic indicators of Madagascar. The study outlines the institutional arrangements for the determination and management of the Malagasy franc, and reviews the foreign exchange market developments. The paper assesses the country's international price competitiveness and developments in the export processing zone. This report also provides a Statistical Appendix for the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet